2015
DOI: 10.1186/s12885-015-1353-3
|View full text |Cite
|
Sign up to set email alerts
|

FGF9 from cancer-associated fibroblasts is a possible mediator of invasion and anti-apoptosis of gastric cancer cells

Abstract: BackgroundCancer-associated fibroblasts (CAFs), which reside around tumor cells, are suggested to play a pivotal role in tumor progression. Here we performed microarray analyses to compare gene expression profiles between CAFs and non-cancerous gastric fibroblasts (NGFs) from a patient with gastric cancer and found that fibroblast growth factor 9 (FGF9) was a novel growth factor overexpressed in CAFs. We then examined the biological effects of FGF9 during progression of gastric cancer.MethodsExpression of FGF9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 31 publications
3
42
0
Order By: Relevance
“…In addition to the previously reported overexpression of Fgf2 and Fgfr2 , we also found that CAFs tended to overexpress Tgfb , Mmp7 , and Fgf9 (Figure A–E). When secreted, these CAF‐secreted factors have previously been shown to support the growth of various tumour types . As lung cancer and alveolar cells in our model both overexpress Fgf9 (and eGfp), we confirmed the absence of any contaminating epithelial cells within our CAF samples using flow cytometry (0% EpCAM + or GFP + cells) and thus confirmed that the CAFs in our model overexpress Fgf9 .…”
Section: Resultssupporting
confidence: 82%
“…In addition to the previously reported overexpression of Fgf2 and Fgfr2 , we also found that CAFs tended to overexpress Tgfb , Mmp7 , and Fgf9 (Figure A–E). When secreted, these CAF‐secreted factors have previously been shown to support the growth of various tumour types . As lung cancer and alveolar cells in our model both overexpress Fgf9 (and eGfp), we confirmed the absence of any contaminating epithelial cells within our CAF samples using flow cytometry (0% EpCAM + or GFP + cells) and thus confirmed that the CAFs in our model overexpress Fgf9 .…”
Section: Resultssupporting
confidence: 82%
“…A previous study showed that FGF9 from cancer-associated fibroblasts may activate invasion ability of GC cells [28]. In our study, we found that knockdown of FGF9 resulted in reduced cell growth and induced apoptosis in GC.…”
Section: Discussionsupporting
confidence: 64%
“…Many reports have illustrated that FGF9 is essential for steroidogenesis and sex determination . However, abnormal expression of FGF9 is involved in different types of cancers . Studies have also shown that endogenous overexpression of FGF9 might cause lung adenocarcinoma, and microRNA‐140‐5p and microRNA‐26a could suppress FGF9 expression to reduce hepatocellular carcinoma and gastric cancer, respectively .…”
Section: Discussionmentioning
confidence: 99%
“…35 Studies have reported that FGF9 participates in palate formation, sex determination and lung development in the embryonic stage and has low expression levels under normal conditions in few adult organs. [36][37][38] However, abnormal expression of FGF9 might cause various cancer formations, [39][40][41][42] and the mechanisms remain elusive.…”
Section: Introductionmentioning
confidence: 99%